Unpacking Chinese Medical Students’ Well-being and Its Relationship with Grit and Resilience - Jia Fu; Ying Wang (SAGE Open)
Enlightened by the tenets of positive psychology (PP), well-being is regarded as a critical construct in the educational situation. The other factor is resilience documented as a precarious value among medical students that will allow them to deal with the challenges faced in both their educations and future professions. Furthermore, grit is another considerable point in the learning process that has been at the center of researchers’ attention in recent years due to its long-run importance; however, what remains ambiguous is the role of grit and resilience in mitigating learners’ well-being among medical students. To this end, 1,088 Chinese medical students (359 males and 729 females) took part in this study. They completed three questionnaires including the resilience scale, grit scale questionnaire, and general well-being scale. Multiple regressions were run and it was revealed that grit and resilience could predict 64.5% of the variance in well-being which was significant. Finally, some implications and recommendations have been presented for language teaching stakeholders in scholastic contexts.